PENGARUH HASIL BELAJAR PRAKTIK KERJA LAPANGAN TERHADAP KESIAPAN KERJA SISWA SEKOLAH MENENGAH KEJURUAN - Nurul Alifa (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2020)
The purpose of this study was to determine, the effect of learning outcomes of fieldwork practices on student work readiness, results of fieldwork practices, and work readiness. This research is an ex-post facto research. The data collection method uses a questionnaire and documentation method. Data analysis techniques used descriptive analysis techniques and hypothesis testing using Product Moment correlation test that was preceded by tests of normality and linearity. The results showed that there was an effect of the results of fieldwork practices on work readiness with a value of robs = 0.613> rtable = 0.297. The determinant coefficient (R2) = 0.376, meaning that the amount of the contribution is 37.6%, while the remaining 62.4% is influenced by other factors, The results of the field work practices are mostly in the high category with a frequency of 86.36%., Work readiness is mostly in the sufficient category with a relative frequency of 50%.